2020
DOI: 10.3390/molecules25214896
|View full text |Cite
|
Sign up to set email alerts
|

Crotalaria verrucosa Leaf Extract Mediated Synthesis of Zinc Oxide Nanoparticles: Assessment of Antimicrobial and Anticancer Activity

Abstract: In this work, we present an ecofriendly, non-hazardous, green synthesis of zinc oxide nanoparticles (ZnO NPs) by leaf extract of Crotalaria verrucosa (C. verrucosa). Total phenolic content, total flavonoid and total protein contents of C. verrucosa were determined. Further, synthesized ZnO NPs was characterized by UV–visible spectroscopy (UV-vis), X-ray diffractometer (XRD), Fourier transform infra-red (FTIR) Spectra, transmission electron microscope (TEM), and Dynamic light scattering (DLS) analysis. UV-vis s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(30 citation statements)
references
References 79 publications
2
26
0
Order By: Relevance
“…Due to the small size of biosynthesized zinc oxide nanoparticles, they provide a high surface area, which leads to more interactions between nanoparticles and bacterial cells, which can be used as an antibacterial agent even at lower dosages. Biosynthesized zinc oxide nanoparticles initially interact with the bacterial plasma membrane, causing nanoparticles to enter the cytoplasm and release metal ions, thereby disrupting the membrane permeability and, finally, causing DNA damage, leading to the death of bacterial cells [ 71 ]. The antibacterial activity demonstrated by zinc oxide nanoparticles synthesized from leaf extracts of Cassia fistula and Melia azadarach have a substantial ability to suppress clinical pathogens (such as E. coli and S. aureus ) compared to traditional drugs, and it was concluded that the synthesis of nanoparticles employing the extracts of medicinal plants could be effective in the treatment of various human infectious diseases [ 126 ].…”
Section: Biomedical Applications Of Plant-mediated Zinc Oxide Nanoparticlesmentioning
confidence: 99%
See 3 more Smart Citations
“…Due to the small size of biosynthesized zinc oxide nanoparticles, they provide a high surface area, which leads to more interactions between nanoparticles and bacterial cells, which can be used as an antibacterial agent even at lower dosages. Biosynthesized zinc oxide nanoparticles initially interact with the bacterial plasma membrane, causing nanoparticles to enter the cytoplasm and release metal ions, thereby disrupting the membrane permeability and, finally, causing DNA damage, leading to the death of bacterial cells [ 71 ]. The antibacterial activity demonstrated by zinc oxide nanoparticles synthesized from leaf extracts of Cassia fistula and Melia azadarach have a substantial ability to suppress clinical pathogens (such as E. coli and S. aureus ) compared to traditional drugs, and it was concluded that the synthesis of nanoparticles employing the extracts of medicinal plants could be effective in the treatment of various human infectious diseases [ 126 ].…”
Section: Biomedical Applications Of Plant-mediated Zinc Oxide Nanoparticlesmentioning
confidence: 99%
“…The small size of zinc oxide nanoparticles, on the other hand, aids in the permeation and retention of nanoparticles within tumorous cells, allowing them to act. The possible mechanisms behind zinc oxide nanoparticles’ selective pH-responsive cytotoxicity towards cancer cells are (1) the pH-dependent rapid dissolution of zinc oxide nanoparticles into the release of Zn 2+ ions under an acidic intracellular environment, which causes oxidative stress (via ROS production) and subsequent cell damage within cancer cells, and (2) the production of a large amount of ROS in cancer cells relative to normal cells; the elevated ROS level then causes mitochondrial dysfunction and activates the intrinsic mitochondrial apoptotic pathway ( Figure 5 ) (Sana et al [ 71 ]. ROS can also mediate cell death via extrinsic necrosis and apoptosis.…”
Section: Biomedical Applications Of Plant-mediated Zinc Oxide Nanoparticlesmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to improve biological applications of Ag-NPs as therapeutic agents, the advancement of environmentally sustainable technology in material synthesis is of significant importance. To overcome their potential hazard and toxic effect, green synthesis have shown exceptional recognition and is preferred over chemical and physical methods because it is cost effective, less toxic, eco-friendly, requires less energy, gives high productivity and significantly biocompatible with high reduction potential (Bhattacharya and Gupta, 2005;Mohanpuria et al, 2008;Prasad, 2014;Thuesombat et al, 2014;Aziz et al, 2015;Aziz et al, 2019;Sana et al, 2020). These biogenic nanoparticles are reported to be synthesized from bacteria (Saifuddin et al, 2009), actinomycetes (Ahmad et al, 2003), plants (Dinesh et al, 2015), sugar (Darroudi et al, 2011), biodegradable polymerschitosan (Venkatesham et al, 2012), which act as both reducing and stabilizing agents (Durán et al, 2011).…”
Section: Introductionmentioning
confidence: 99%